Analysis of the Effect of Technology on the Growth of the Information and Communication Sector in the Bali Province 2016-2021 - Milan Puji; Krismanti Tri Wahyuni (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Technology continues to develop and drive economic growth. Bali, as a province that is open to foreign tourists in Indonesia, has a great opportunity to adopt technology more quickly. This study aims to analyze the effect of technology development as well as other variables such as the number of workers in the ICT sector, household consumption for Information and Communication Technology (ICT), and the amount of accommodation for Gross Regional Domestic Product (GRDP) of the ICT Sector in districts/cities of Bali Province. The analysis to be used is descriptive and inferential analysis with panel data regression from regencies/cities in Bali Province period 2016-2021. The model used is the fixed effect model. In general, the GRDP of the ICT Sector continues to increase, but its growth is decreasing every year. Meanwhile, technological developments in Bali Province tend to increase every year. With a significance level of 5 percent, the percentage of e-commerce users, the percentage of ownership of cell phones, and the number of accommodations have a significant positive effect on the GRDP of the ICT sector. Technological progress has not been fully utilized, therefore the GRDP growth of the ICT sector tends to decrease every year.